SCHOOL STRATEGY IN FORMING STUDENT CHARACTER IN ELEMENTARY SCHOOLS - Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2022)
The purpose of the research is to learn how the elementary school uses the development of religious, orderly, and environmentally conscious characters to mold the character of its children. This study used a descriptive qualitative methodology that included the processes of conducting interviews, observations, and documentation. The study's findings indicated that the implementation of the school's strategy for developing students' character through the development of religious character, discipline, and environmental care was supported by good planning, beginning with activities inside and outside the classroom, adequate facilities, and infrastructure.